pre-calculus

what is the F-^1

of

6/x+4

  1. 👍 0
  2. 👎 0
  3. 👁 36
asked by kelly
  1. Your notation is confusing and your equation is ambiguous without parentheses.

    If F(x) = 6/(x+4) = y,

    the inverse function F^-1 (x) is the operation that, if applied to y, will give you x.
    x +4 = 6/y
    x = (6/y) -4

    Finally, switch variables.

    F^-1(x) = (6/x) - 4

    Note that if you apply this inverse function to 6/(x+4), you get back x.

    1. 👍 0
    2. 👎 0
    posted by drwls

Respond to this Question

First Name

Your Response